Cost of providing emergency obstetric care in Tanzania's Kigoma region. (3rd July 2019) - Mengistu, Tewodaj; Berruti, Andrés; Krivelyova, Anna; Swor, Meghan; Waite, Rachel; Maro, Godson
Summary: Background: The provision of Emergency Obstetric and Neonatal Care (EmONC) is critical for reducing maternal mortality, yet little is known about the costs of EmONC services in developing countries. This study estimates these costs at six health facilities in Tanzania's Kigoma region. Methods: The study took a comprehensive programmatic approach considering all sources of financial and in‐kind support over a 1‐year period (1 July 2012 to 30 June 2013). Data were collected retrospectively and costs disaggregated by input, sources of support, programmatic activity, and patient type (nonsurgical, surgical patients, and among the latter patients undergoing caesarean sections). Results: The median per‐patient cost across the six facilities was $290. Personnel and equipment purchases accounted for the largest proportions of the total costs, representing 32% and 28%, respectively. Average per‐patient costs varied by patient type; cost per nonsurgical patient was $80, $258 for surgical patients and $426 for patients undergoing caesarean sections. Per‐patient costs also varied substantially by facility type: mean per‐patient cost at health centres was $620 compared with $169 at hospitals. Conclusions: This study provides the first cost estimates of EmONC provision in Kigoma. These estimates could inform programme planning and highlight areas with potential scope for cost reductions.